Major Cities of the Biblical World (1985)
32-48: E. Yamauchi, Babylon; 96-106: G. H. Livingston, Damascus; 107-118: M. J. Horsnell, Ebla; 156-169: B. J. Beitzel, Mari; 180-189: M. R. Wilson, Nineveh; 190- 197: P. W. Gaebelein, Nuzi; 275-284: M. J. Selman, Ur.